2017
DOI: 10.1108/pr-05-2015-0138
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the implications of the influence of organisational culture on work-life balance practices

Abstract: Purpose -Whilst significant evidence of western work-life balance (WLB) challenges exists, studies that explore Sub-Saharan Africa (SSA) are scarce. This article explores how organisational culture in Nigerian medical organisations influences doctors' WLB and examines the implications of supportive and unsupportive cultures on doctors' WLB.Methodology -The paper uses qualitative data gleaned from semi-structured interviews of 60 medical doctors across the six geo-political zones of Nigeria in order to elicit W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
60
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(64 citation statements)
references
References 76 publications
4
60
0
Order By: Relevance
“…Its affairs are regulated by the Nigerian Medical and Dental Council. Records show that Nigeria has the largest number of doctors in Africa (Adisa et al, 2017). However, Nigeria's political instability, economic downturn, and poor working conditions are causing many professionals, especially medical doctors, to migrate to 'greener pastures' with better career and WLB prospects (Mushfiqur et al, 2018).…”
Section: The Study Contextmentioning
confidence: 99%
“…Its affairs are regulated by the Nigerian Medical and Dental Council. Records show that Nigeria has the largest number of doctors in Africa (Adisa et al, 2017). However, Nigeria's political instability, economic downturn, and poor working conditions are causing many professionals, especially medical doctors, to migrate to 'greener pastures' with better career and WLB prospects (Mushfiqur et al, 2018).…”
Section: The Study Contextmentioning
confidence: 99%
“…Employees that work in traditional organisations are naturally expected to experience difficulties in combining their work and nonwork responsibilities due to the required commitments and expectations from their various employers (see Adisa et al, 2017;Adisa et al, 2016;Eikhof et al, 2007). One would expect that entrepreneurs would enjoy a great deal of WLB because of the self-employed nature of their business ventures.…”
Section: Work Is Prioritised Over Lifementioning
confidence: 99%
“…However, the implication of these factors on the boundaries between entrepreneurs' work and nonwork lives is yet to be fully explored. Helping employees to achieve a satisfactory balance between their work and personal lives has been one of the dominant issues in human resource management (HRM) in recent years (Adisa et al, 2017;Parris et al, 2008). Indeed, many researches have investigated employees' work-life balance (WLB) within the organisational setting (Adisa et al, 2017;Carlson et al, 2009;Eby et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior research has demonstrated that organization can reduce faculty members burnout (Padilla and Thompson, 2016) and turnover (Allen, 2001) through provision of WLBP (e.g., flexi-time, telecommuting) because such practices provide employees with the flexibility and autonomy in balancing their work and non-work lives (Onken-Menke et al, 2018). In contrast, lack of WLBP such as long working hours reduces employees' time to spend on social and family activities (Chiang et al, 2010), negatively affect WLB (Adisa et al, 2017) and result in stress and turnover intention (Allen, 2001). In sum, a review of the literature and previous studies demonstrate that WLBP is an important element of employees' turnover intention.…”
Section: Work-life Balance Practices (Wlbp) and The Intention To Leavementioning
confidence: 99%